MENILAI DAMPAK EKONOMI DARI FAKTOR MICE TERHADAP PERTUMBUHAN PARIWISATA: WAWASAN DARI GEOPARK KALDERA TOBA - Siagian, Desmon Gunadi; Sirait, Katrin Jenny (JURNAL ILMIAH EDUNOMIKA, 2024)
This study analyzes the impact of MICE (Meeting, Incentive, Convention, Exhibition) factors on the economic growth of the Toba Caldera Geopark tourism destination. To support the economic growth of the Geopark, it is essential to have robust infrastructure, including adequate accessibility, convention centers with quality accommodation options, three to five-star hotels, attractive destinations with numerous facilities, parking areas, and skilled local PCOs (Professional Conference Organizers). The research background highlights issues related to the impact of MICE factors on the economic development of tourism destinations. Besides infrastructure, the products offered must have value and can be packaged to provide added value. This includes not only competitive pricing but also packaging and the product's connection to the local environment. Data collection methods used in this research include observation and questionnaires. Informants comprised various stakeholders in the MICE industry, such as the Medan City Tourism Office, event organizers, and businesses involved in tourism, including hotels, restaurants, ATMs, money changers, travel agencies, souvenir shops, transportation providers, guides, meeting organizers, congress organizers, and incentive travel organizers. The results show that accessibility does not have a direct and significant impact on the economic growth of the Toba Caldera Geopark tourism destination. Similarly, accommodation facilities do not directly and significantly influence economic growth. However, information has a positive and significant impact on the economic growth of the Toba Caldera Geopark tourism destination.